2015
DOI: 10.1038/ncb3258
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatic breaks move to the nuclear periphery to continue recombinational repair

Abstract: Heterochromatin mostly comprises repeated sequences prone to harmful ectopic recombination during double-strand break (DSB) repair. In Drosophila cells, ‘safe’ homologous recombination (HR) repair of heterochromatic breaks relies on a specialized pathway that relocalizes damaged sequences away from the heterochromatin domain before strand invasion. Here we show that heterochromatic DSBs move to the nuclear periphery to continue HR repair. Relocalization depends on nuclear pore and inner nuclear membrane protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
484
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 240 publications
(502 citation statements)
references
References 81 publications
(169 reference statements)
18
484
0
Order By: Relevance
“…In flies, it was shown that dRad60 (the homolog of Rad60 in fission yeast, Esc2 in budding yeast, and NIP45 in humans) contributes to the shift of DSBs away from heterochromatin in irradiated Drosophila cells (Ryu et al 2015). This class of factors, called RENi, is thought to stimulate the ubiquitination activity of the Slx5/8 STUbL in yeast (Prudden et al 2007).…”
Section: Polysumoylation Is Required For Slx5 Recruitment and Dsb Relmentioning
confidence: 99%
See 4 more Smart Citations
“…In flies, it was shown that dRad60 (the homolog of Rad60 in fission yeast, Esc2 in budding yeast, and NIP45 in humans) contributes to the shift of DSBs away from heterochromatin in irradiated Drosophila cells (Ryu et al 2015). This class of factors, called RENi, is thought to stimulate the ubiquitination activity of the Slx5/8 STUbL in yeast (Prudden et al 2007).…”
Section: Polysumoylation Is Required For Slx5 Recruitment and Dsb Relmentioning
confidence: 99%
“…Although Rad52 SUMOylation influenced damage relocation from the nucleolus to the nucleoplasm (Torres-Rosell et al 2007), Rad52 was not needed for the relocation of a euchromatic DSB to pores (Horigome et al 2014). In flies, the STUbL subunit Dgrn, along with the SMC5/6 complex, was necessary for DSB relocation away from heterochromatin (Chiolo et al 2011;Ryu et al 2015). This shift required the STUbL interactor Rad60 (ScEsc2/HsNIP45) and the Nup84 pore complex (Ryu et al 2015).…”
mentioning
confidence: 99%
See 3 more Smart Citations